2021
DOI: 10.1159/000514384
|View full text |Cite
|
Sign up to set email alerts
|

Bufavirus, Cosavirus, and Salivirus in Diarrheal Italian Infants

Abstract: Three newly discovered viruses have been recently described in diarrheal patients: Cosavirus (CosV) and Salivirus (SalV), 2 picornaviruses, and bufavirus (BuV), a parvovirus. The detection rate and the role of these viruses remain to be established in acute gastroenteritis (AGE) in diarrheal Italian infants. From November 2016 to November 2017, stool samples were collected from 160 children <5 years old suffering from AGE and attending the Children’s Hospital in Turin, Italy. During the study period, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Before the implication of Rotavirus vaccination, Rotavirus was the leading cause of viral GE, while other enteric viruses, such as Noroviruses, Astroviruses, and Human adenoviruses, are now the most prevalent viruses causing GE ( 3 ). Besides the aforementioned enteric viruses, the list of enteric viruses is continuously growing due to the discovery of emerging viruses ( 4 , 5 ). Since still 40% of cases of GE are of unknown etiology ( 6 ), these newly discovered viruses may likely be involved in causing the GE ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Before the implication of Rotavirus vaccination, Rotavirus was the leading cause of viral GE, while other enteric viruses, such as Noroviruses, Astroviruses, and Human adenoviruses, are now the most prevalent viruses causing GE ( 3 ). Besides the aforementioned enteric viruses, the list of enteric viruses is continuously growing due to the discovery of emerging viruses ( 4 , 5 ). Since still 40% of cases of GE are of unknown etiology ( 6 ), these newly discovered viruses may likely be involved in causing the GE ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…46,47 Our findings showed a positivity rate of 2.1% for SalV by qPCR, a value similar to that found in other studies, such as in China 48 and Tunisia, 14 where the prevalence ranged from 0.1% to 8.8% in patients with AG. Daprà et al 49 Regarding AiV, the data are similar; other studies also identified a low percentage, remembering that this virus was first detected in Nigeria (0.97%, 1/103). 50 In Brazil, a study on the prevalence of AiV in samples from children with AG showed a positivity of 0.4% (1/250).…”
Section: Especie (%) Sorotype N Of Positive Samples (%)mentioning
confidence: 55%
“…Our findings showed a positivity rate of 2.1% for SalV by qPCR, a value similar to that found in other studies, such as in China 48 and Tunisia, 14 where the prevalence ranged from 0.1% to 8.8% in patients with AG. Daprà et al 49 observed a SalV detection rate of 0.5% in stool samples from children under 5 years of age in Italy.…”
Section: Discussionmentioning
confidence: 99%
“…Infectious acute gastroenteritis (AGE) represents a world public health relevant problem being an important cause of children mortality in developing countries and the main cause of pediatric morbidity worldwide. [1][2][3][4][5][6][7][8][9][10] The pathogens mainly involved in the episodes of AGE are the enteric viruses, which account for about 70% of the cases and are responsible every year for millions of children infections. 1,11 Gastroenteritis is usually characterized by mild symptomatology lasting a couple of days, with symptoms including diarrhea, abdominal pain, nausea, vomiting.…”
Section: Introductionmentioning
confidence: 99%